Penerapan Model UTAUT 2 Untuk Menjelaskan Niat Dan Perilaku Penggunaan E-Money di Kota Denpasar - Risma Dwinda Putri, Ni Komang; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the factors that influence the intentions and behavior of e-money use by applying the UTAUT2 model. UTAUT2 used in this study are performance expectations, business expectations, socio-cultural factors, facilitating conditions, hedonic motivation, price values, and habits. This research was conducted in the city of Denpasar. Determination of the sample is done by accidental sampling technique. Data collection is done by distributing questionnaires online. The analysis technique used is multiple linear regression. This study shows that the intention to use e-money is influenced by facilitating conditions, hedonic motivation, and price values, while performance expectations, business expectations, and socio-cultural factors have no effect. The results of this study also show that e-money usage behavior is influenced by habits and intentions of use, while the conditions that facilitate it have no effect. Keywords: UTAUT2; Intention to Use E-Money; E-Money Usage Behavior.